Modulation of Ion Channels in the Superior Cervical Ganglion Neurons by Myocardial Ischemia and Fluvastatin Treatment - Cheng, Lijun; Wang, Xinghua; Liu, Tong; Tse, Gary; Fu, Huaying; Li, Guangping (Frontiers in Physiology, 2018)
Background: The superior cervical ganglion (SCG) of the autonomic nervous system plays an important role in different cardiovascular diseases. In this study, we investigated the effects of ischemia and fluvastatin treatment on the ion channel characteristics of SCG neurons in a rabbit myocardial ischemia (MI) model. Methods: MI was induced by abdominal subcutaneous injections of isoproterenol (ISO). The properties of the delayed rectifier potassium channel current (IK), sodium channel current (INa), and action potential (APs) on isolated SCG neurons in the control, MI-7d, MI-14d, fluvastatin-7d (fluvastatin pretreated 14 days and treated 7 days after ISO-induced MI), and fluvastatin-14d (fluvastatin pretreated 14 days and treated 14 days after ISO-induced MI) groups were studied. In addition, the RNA expressions of KCNQ3 and SCN9A in the SCG tissue were determined by performing real-time PCR. Intracellular calcium concentration was monitored using laser scanning confocal microscopy. Results: Compared with the control group, the current amplitude of IK and INa were increased in the MI-7d and MI-14d groups. KCNQ3 RNA (corresponding to channel proteins of IK) expression and SCN9A RNA (corresponding to channel proteins of INa) expression were also increased in MI groups. Activation and inactivation curves for INa in the two MI groups shifted negatively compared with the control group. These changes were reversed by fluvastatin treatment. Intracellular calcium concentration in SCG neurons was not altered significantly by MI or fluvastatin treatment. By contrast, increased AP amplitude and shortened APD90 were observed in the MI-7d and MI-14d groups. These changes were reversed in the fluvastatin-treated MI group. Conclusion: Fluvastatin treatment partly reversed the characteristics of SCG neurons in MI. The ion channel of SCG neurons could be one of the potential targets of fluvastatin in treating coronary heart diseases.